Development of Monoclonal Antibody Based Enzyme-Linked Immunosorbent Assay for Neonicotinoid Insecticides Thiamethoxam Residue in Environmental Water Samples - Li, G.L.; Li, X.A.; Chen, X.L. (Asian Journal of Chemistry, 2015)
This work describes the analytical performance of newly developed method-based enzyme-linked immunosorbent assay (ELISA) for neonicotinoid insecticide thiamethoxam to effectively exploit as a rapid and simple detection technology for pesticide residue on the scenes of the environmental water monitoring samples. The enzyme-linked immunosorbent assay represents the satisfactory analytical characteristics (IC50 value, 0.0255 mg L-1; limit of detection, 0.001 mg L-1) to detect thiamethoxam at the maximum residue limits (MRL) or there about in samples. For the enzyme-linked immunosorbent assay analysis, acetonitrile showed the lowest influence on the assay performance was selected as the best extraction and the final concentration in the well could be up to 5 % (v/v) without any negative influence on the enzyme-linked immunosorbent assay. Dilution of sample extracts with water was effective in eliminating matrix interference. Average recoveries from thiamethoxam-spiked environmental water samples were > 75 % using a rapid and simple extraction method with hand shaking for 5 min. Analytical results obtained from the enzyme-linked immunosorbent assay were comparable to those obtained from the conventional HPLC method. These findings strongly indicate that the proposed method-based enzyme-linked immunosorbent assay for determination of thiamethoxam residue in environmental water may be routinely employed as a rapid, simple and quantitative preliminary screening method for the monitoring of safety of environmental water.